2011
DOI: 10.1113/jphysiol.2011.211094
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic activation of Ca2+‐activated Cl current in interstitial cells of Cajal

Abstract: Non-technical summary Interstitial cells of Cajal (ICC) are tightly associated with excitatory and inhibitory motor neurons in the gastrointestinal tract, and these cells are also connected electrically to smooth muscle cells. We have suggested that ICC participate in responses to neurotransmitters released from neurons that drive motility and help move nutrients and wastes through the gut. We studied responses of isolated ICC to cholinergic neurotransmitter and found that a Ca 2+ -activated Cl − current is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
93
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 40 publications
2
93
0
Order By: Relevance
“…A more recent study showed that Ca 2+ -activated chloride channels are activated in ICC in response to cholinergic neurotransmission. 205 The channel involved is likely to be ANO1 expressed exclusively in ICC in the GI tract. 67,106,107,131 Additionally, inhibition of a basally active Ca 2+ -activated chloride channel has been suggested to account for part of the response to nitrergic stimulation.…”
Section: Functional Evidence Demonstrating the Importance Of Interstimentioning
confidence: 99%
“…A more recent study showed that Ca 2+ -activated chloride channels are activated in ICC in response to cholinergic neurotransmission. 205 The channel involved is likely to be ANO1 expressed exclusively in ICC in the GI tract. 67,106,107,131 Additionally, inhibition of a basally active Ca 2+ -activated chloride channel has been suggested to account for part of the response to nitrergic stimulation.…”
Section: Functional Evidence Demonstrating the Importance Of Interstimentioning
confidence: 99%
“…To date, only one transcriptomic analysis of ICC has been achieved after enrichment and purification of cell samples through fluorescence-activated cell sorting [9], but the implementation and validation of such a method requires specialized equipment and considerable economic investment. With the availability of transgenic mice with copGFP-expressing ICC [10], primary cultures have been used to improve identification in electrophysiological or immunohistochemical analyses [11,12] but not in single cell characterization. One alternative for the molecular analysis of ICC is the single-cell RT-PCR technique, which allows the collection of individual cells from a mixed culture [13].…”
Section: Introductionmentioning
confidence: 99%
“…STICs generate depolarization, activate Ca 2ϩ entry, and synchronize the openings of channels responsible for STICs, generating slow wave currents. STICs and slow wave currents are due to the activation of Ca 2ϩ -activated Cl Ϫ channels (CaCC) encoded by Ano1 (11,14,53,54). While the mechanism and ionic conductance responsible for STICs and slow wave currents have been described, the mechanisms responsible for delivering Ca 2ϩ to ANO1 channels are not fully understood and have not been studied directly at the level of single ICC.…”
mentioning
confidence: 99%
“…For the experiments in this study, we used cells from Kit ϩ/copGFP mice, which have constitutive expression of copGFP in ICC, to investigate the effects of Ca 2ϩ store-active drugs on STICs and slow wave currents (53,54). We studied the effects of blocking Ca 2ϩ uptake into stores and of blocking release of Ca 2ϩ from IP 3 -dependent and ryanodine-sensitive channels to test directly the hypothesis that Ca 2ϩ release from the endoplasmic reticulum (ER) is fundamental to pacemaker activity in ICC.…”
mentioning
confidence: 99%